2022
DOI: 10.3324/haematol.2022.280629
|View full text |Cite
|
Sign up to set email alerts
|

A novel BCMA CAR-T-cell therapy with optimized human scFv for treatment of relapsed/refractory multiple myeloma: results from phase I clinical trials

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the phase I studies (NCT03302403, NCT03380039, NCT03716856), 24 patients received a dose ranging from 0.5 to 1.8 × 10^6 CT053 cells, the ORR was 87.5%, indicating a high rate of response to CT053 treatment, with 79.2% patients achieved CR (12.5%) or sCR (66.7%), demonstrating deep and durable responses, and the median follow-up time was 17.4 months, the mPFS was 18.8 months and the mDOR was 21.8 months. Anti-drug antibody (ADA) was not detected in patients after infusion, suggesting no significant immunogenicity associated with CT053 treatment, and CT053 demonstrated strong efficacy and a good safety profile for patients with RRMM [ 250 ].…”
Section: Targeted Immunotherapymentioning
confidence: 99%
“…In the phase I studies (NCT03302403, NCT03380039, NCT03716856), 24 patients received a dose ranging from 0.5 to 1.8 × 10^6 CT053 cells, the ORR was 87.5%, indicating a high rate of response to CT053 treatment, with 79.2% patients achieved CR (12.5%) or sCR (66.7%), demonstrating deep and durable responses, and the median follow-up time was 17.4 months, the mPFS was 18.8 months and the mDOR was 21.8 months. Anti-drug antibody (ADA) was not detected in patients after infusion, suggesting no significant immunogenicity associated with CT053 treatment, and CT053 demonstrated strong efficacy and a good safety profile for patients with RRMM [ 250 ].…”
Section: Targeted Immunotherapymentioning
confidence: 99%
“…Reduction of CRS using optimized L17 CD19 CAR T cells generated via studies of ScFv activity shows a potential tool for tumor therapy. To treat MM optimized fully human ScFv CT053 has been studied along with clinical trials [ 34 ] proving the fact that ScFv could optimize the activity of CAR T cells. KHYG-1 NK/T cell line is important in case of cell culture and gene transduction.…”
Section: Scfv Modifications Using Crisprmentioning
confidence: 99%
“…which proves the above mentioned fact. By using CRISPR ScFv can be modified to optimize the activity of CAR T cells [14,20,34,37].…”
Section: Scfv Modifications Using Crisprmentioning
confidence: 99%
“…Fully humanized CAR constructs targeting BCMA include orvacabtagene autoleucel (JCARH125, orva-cel, no longer under development), FHVH-BCMA-T, zevorcabtagene autoleucel (CT053), CT103A, and CC- 98633 ( 55 61 ). In two phase 1 trials of CT053 ( n = 24) and CT103A ( n = 71) respectively, ADAs have been reported in fewer than 5% of patients ( 59 , 60 ). Another promising CAR-T therapy under early investigation is CART-ddBCMA, where the BCMA-binding domain has been chosen from a synthetic protein library followed by subsequent mutagenesis and testing to minimize rates of ex vivo immunogenicity ( 62 ).…”
Section: Better Mileage: Longer Duration Of Responsesmentioning
confidence: 99%